Targeting PI3K/mTOR signaling in cancer - Alexandre Arcaro (Frontiers Research Topics, 2014)
The phosphatidylinositol 3-kinase (PI3K)/mTOR pathway integrates signals from growth factors with nutrient signals and other conditions and controls multiple cell responses, including proliferation, survival and metabolism. Deregulation of the PI3K pathway has been extensively investigated in connection to cancer. Somatic or inherited mutations frequently occur in tumor suppressor genes (PTEN, TSC1/2, LKB1) and oncogenes (PIK3CA, PIK3R1, AKT) in the PI3K/mTOR pathway. The fact that the PI3K/mTOR pathway is deregulated in a large number of human malignancies, and its importance for different cellular responses, makes it an attractive drug target. Pharmacological PI3K inhibitors have played a very important role in studying cellular responses involving these enzymes. Currently, a wide range of selective PI3K inhibitors have been tested in preclinical studies and some have entered clinical trials in oncology. Rapamycin and its analogs targeting mTOR are effective in many preclinical cancer models. Although rapalogs are approved for the treatment of some cancers, their efficacy in clinical trials remains the subject of debate. Due to the complexity of the PI3K/mTOR signaling pathway, developing an effective anti-cancer therapy remains a challenge. The biggest challenge in curing cancer patients with various signaling pathway abnormalities is to target multiple components of different signal transduction pathways with mechanism-based combinatorial treatments.